Supports and Barriers Regarding The Iron-Folic Acid Supplementation Adherence Level in Anemic Pregnant Women: Indonesian’s Perspective - Rizka Novia Atmadani; Akrom Akrom; Dhea Ananda; Laila Yoga Saputri; Alvina Arum Puspitasari; Siti Urbayatun (Media Kesehatan Masyarakat Indonesia, 2024)
Anemia is a worldwide public health issue that affects various groups in low, middle, and high-income nations. Anemia is linked to pregnancy and is influencing poor cognitive and motor development outcomes in children. A recommended intervention to reduce anemia prevalence during pregnancy is the universal administration of Iron-Folic Acid (IFA) supplements. This study investigated supports and barriers regarding iron-folic acid supplementation adherence levels in pregnant women recorded in public health centers in Malang, Indonesia. This research was conducted using qualitative methods with in-depth interviews using semi-structured open-ended questions from July to September 2023. Twenty-five participants from four public health centers was included. The interview guide's content was developed using World Health Organization’s framework as well as other pertinent themes. Data analysis was processed from verbal record transcription, generating the codes into the outcomes. Five main themes with a total of eleven subthemes were highlighted from interview process. These themes was further classified into barriers and supports. Side effect, forgetfulness, boredom, laziness, and insufficient understanding of disease recorded as barriers. In contrast, husband and family support, health care team motivation, affordability of access, knowledge and education background included in supports. These findings enlighten the barriers encountered by the pregnant women in IFA supplementation adherence. However, the effectiveness of treating anemia during pregnancy might be influenced by fundamental elements that support IFA supplementation adherence. Therefore, to tackle the this issue, the pregnant women requires a proper therapy and all key points mentioned in support group must be applied.